PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA TOPIK EKOSISTEM MELALUI PENGGUNAAN MEDIA BERVARIASI - Nurhana; Fajeri Arkiang (Scientica Education Journal, 2024)
This study aims to analyze the effect of using varied media on improving learning outcomes for fifth grade students in elementary school of UPT SD Inpres Sali-Sali in the science subject on the topic of Ecosystems. The type of the research is classroom action research. This classroom action research was carried out in two cycles, and each cycle consisted of four stages, namely planning, action, observation, and reflection. The research subjects were fifth grade students of UPT SD Inpres Sali-Sali, Patampanua District, Pinrang Regency, in the odd semester of the 2022/2023 school year. The technique of the data collection was carried out by observation and test. The Processing of data in this research is qualitative and quantitative. The results showed that the learning outcomes in science subjects on the topic of ecosystems for fifth grade UPT SD Inpres Sali-Sali after taking the evaluation test at the end of the learning activities increased in the first cycle of 71.67% to 85% in cycle II with a percentage of 50% in cycle I and 100% percent in cycle II.